A research paper on the immunomodulatory and anti-inflammatory activities of olive tree (Olea europaea L.) leaf - Beyaz, Seda; Gok, Ozlem; Aslan, Abdullah (Pamukkale University, 2022)
Olive tree (Olea europaea L.) leaf is known to have a number of bioactive properties being antioxidant, antihypertensive, antiatherogenic, antiinflammatory, antifungal, antiviral and antimicrobial. In this study, the immunomodulatory roles of Olive tree (Olea europaea L.) leaf against oxidative damage caused by carbon tetrachloride (CCl4) in Saccharomyces cerevisiae were investigated. In the study, four groups were formed; namely, (i) Control Group: Yeast only planted group; (ii) CCl4Group: Group given CCl4 (15 mM); (iii) Olive Tree Leaf Group: The group given olive tree leaf (10%); and (iv) Olive Tree Leaf + CCl4Group: Olive tree leaf (10%) + CCl4(15 mM) given group. Cultures of Saccharomyces cerevisiae were grown at 30°C for 1, 3, 5, and 24 hours. Malondialdehyde (MDA), glutathione levels (GSH), cell growth and catalase (CAT) activity measurements were determined by spectrophotometer. Total protein concentrations were determined by SDSPAGE electrophoresis and the Bradford protein method. According to the results obtained; compared to the CCl4group, cell growth (1, 3, 5 and 24 hours), total protein synthesis, and GSH and CAT activities (24 hours) increased in olive tree leaf groups, while MDA level (24 hours) decreased. Thanks to its strong bioactive properties, olive tree leaf has been found to increase cell growth and total protein synthesis by decreasing CCl4induced oxidative stress in Saccharomyces cerevisiae culture. It has been concluded that if the olive tree leaf is used regularly, it will be beneficial in eliminating many health problems. © 2022 Authors. All rights reserved.
Keywords: Oleuropein; Olive tree leaf; Oxidative stress; Polyphenol; Saccharomyces cerevisiae